Improving Student Learning Outcomes in Pancasila Education Subjects Using Problem-Based Learning Models in Class VII.4 SMP Negeri 33 Palembang - Salsadila, Amelya; Chotimah, Umi; Hasna, Nyimas Nuria (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research uses collaborative classroom action research (PTK) with the Kemmis and McTanggart model Through this research, the aim is to determine the effect of implementing the problem-based learning in the subjects of Civic Education for material on the history of the birth of Pancasila as the basis of the State on the learning outcomes of class VII 4 students at SMP Negeri 33 Palembang. Furthermore, data analysis in this research uses quantitative analysis based on data assessing student learning outcomes in class VII.4 of SMP Negeri 33 Palembang. Based on the results of research conducted in class VII.4 by applying a problem-based learning model shows an increase in student learning outcomes in class VII.4, namely 90% with a very good predicate with the percentage of students who received grades according to the passing grade in cycle 1, namely 70%. Then continued in cycle 2, the increase in learning outcomes for class VII.4 students reached 90% and the presentation of students who reached the passing grade was 96%.